Rilmenidine treatment in hypertensive patients with cerebrovascular transient ischemic attacks - A. P. Kondrakhin; G. N. Gorokhovskaya; A. I. Martynov (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To assess effectiveness of rilmenidine treatment in arterial hypertensive (AH) patients with cerebrovascular transient ischemic attacks (TIA). Material and methods. The study included 39 patients with Stage I-III AH, combined with TIA: 6 males and 33 females; mean age 47±2.7 years. At baseline and after 4 weeks of rilmenidine monotherapy (1 mg/d), 24-hour blood pressure monitoring (BPM) was performed; beta-adrenoreceptivity of red cell membranes (b-ARM) was measured; psychological status and quality of life (QoL) by DISS (Disability Scale) were assessed. Results. According to 24-hour BPM results, rilmenidine therapy was associated with statistically significant (р<0.01) antihypertensive effect in Stage III AH patients. In participants with Stage I-II AH, circadian BP profile (BP CP) was normalized without statistically significant BP decline. At baseline, b-ARM was increased in all patients, that could be regarded as a sign of enhanced sympatho-adrenal activity. Rilmenidine (1 mg/d) substantially reduces hypersympathicotony, manifested in b-ARM decrease during the therapy. QoL also significantly improved during rilmenidine therapy (р<0.01). Conclusion. Rilmenidine reduced BP level, benefited BP CP, decreased sympathicoadrenal system activity, and improved QoL in AH patients with TIA.